Toll-like receptor 7 governs interferon and inflammatory responses to rhinovirus and is suppressed by IL-5-induced lung eosinophilia. Issue 9 (24th June 2015) - Hatchwell, Luke; Collison, Adam; Girkin, Jason; Parsons, Kristy; Li, Junyao; Zhang, Jie; Phipps, Simon; Knight, Darryl; Bartlett, Nathan W; Johnston, Sebastian L; Foster, Paul S; Wark, Peter A B; et al.
Abstract : Background: Asthma exacerbations represent a significant disease burden and are commonly caused by rhinovirus (RV), which is sensed by Toll-like receptors (TLR) such as TLR7. Some asthmatics have impaired interferon (IFN) responses to RV, but the underlying mechanisms of this clinically relevant observation are poorly understood. Objectives: To investigate the importance of intact TLR7 signalling in vivo during RV exacerbation using mouse models of house dust mite (HDM)-induced allergic airways disease exacerbated by a superimposed RV infection. Methods: Wild-type and TLR7-deficient ( Tlr7 −/− ) BALB/c mice were intranasally sensitised and challenged with HDM prior to infection with RV1B. In some experiments, mice were administered recombinant IFN or adoptively transferred with plasmacytoid dendritic cells (pDC). Results: Allergic Tlr7 −/− mice displayed impaired IFN release upon RV1B infection, increased virus replication and exaggerated eosinophilic inflammation and airways hyper reactivity. Treatment with exogenous IFN or adoptive transfer of TLR7-competent pDCs blocked these exaggerated inflammatory responses and boosted IFNγ release in the absence of host TLR7 signalling. TLR7 expression in the lungs was suppressed by allergic inflammation and by interleukin (IL)-5-induced eosinophilia in the absence of allergy. Subjects with moderate-to-severe asthma and eosinophilic but not neutrophilic airways inflammation, despite inhaled steroids, showed reduced TLR7 and IFNλ2/3 expression in endobronchial biopsies. Furthermore, TLR7 expression inversely correlated with percentage of sputum eosinophils. Conclusions: This implicates IL-5-induced airways eosinophilia as a negative regulator of TLR7 expression and antiviral responses, which provides a molecular mechanism underpinning the effect of eosinophil-targeting treatments for the prevention of asthma exacerbations.